Legal requirements for reporting clinical cases to the South African police or social services - Dirk T. Hagemeister; William Oosthuizen; Bridgette Mokae (South African Family Practice)
Medical confidentiality is the cornerstone for a trustful relationship between patients and the health professionals attending to them. However, when history or clinical findings suggest certain offenses, statutory laws (Children’s Act, Older Persons Act, Mental Health Care Act, Sexual Offenses Act) establish a legal obligation for health professionals to report suspected instances of abuse to the police or alternatively, in some cases, to a designated social worker. Given the high rate of domestic violence and abuse in South Africa, health professionals are most likely to encounter such situations. Many clinicians are oblivious of the obligations, exposing themselves to possible liability and their patients to potential additional harm. This article aims to demonstrate the reporting requirements under the respective acts through case scenarios. Finally, the advantages and disadvantages of the existing legal setting are discussed briefly.